Factors affecting sclerotinia stem rot infections in canola - Bennett, Sarita; Brooks, Kyran; Ashworth, Michael; Denton-Giles, Matthew; Michael, Pippa (2018)
Key messages 1. When conditions are ideal for canola, over half of the Sclerotinia sclerotiorum lesions can be removed from the stubble following Harvest Weed Seed Control (HWSC) guidelines. 2. The numbers of sclerotes left in the soil following a badly infected sclerotinia stem rot crop is highly variable, but can be significant in patches. Rotation of canola with non-host crops is therefore recommended. 3. Even in a dry and late start to the season sclerotinia stem rot infection was recorded in up to 10% of plants, however the severity of infection and subsequent yield loss was less. 4. It is estimated that, if a better understanding of factors affecting sclerotinia stem rot infection of canola led to improved management of the disease and an increase in yield, by as little as 1%, then the benefits to WA grain growers will be close to $1.5 million per annum.